Students' Writing Skill through Text Oriented Material Strategy at Senior High School 2 Pasarwajo - Sri Noviyanti; Asrun Lio; Kamaluddin Kamaluddin (Journal of Language Education and Educational Technology (JLEET), 2022)
The objective of this study was to identify how teachers implemented text-based material in teaching writing in English class, how did the students enhance their writing competence through text oriented material and how the students’ writing performance through text oriented material. This research used mix method which explored the students’ performance in enhancing their writing skill through text oriented material strategy in second grade of SMAN 2 Pasarwajo. Moreover, class XII IPA 1 and IPA 2 students were selected as the respondent of this study which consisted of 52 students. The data in this study was quantitative and qualitative data; the quantitative data was gained from the students’ responses in the distributed questionnaire and the qualitative data was gained from the result of document analysis and observation. To analyze the quantitative data, the researcher used the computational calculation of the SPSS program (Statistical Program for Social Science) to process statistical data accurately and quickly into various required outputs to draw a conclusion. The result of this study shows that text-oriented material is an effective approach to enhance students' competence in writing analytical expositions. students' effort in improving their writing skills through text-oriented material strategy can be seen in their general writing strategy, pre-writing activities, during writing, after writing activities, and writing through text-oriented material. Overall, using text-oriented material as an approach in teaching analytical exposition is beneficial for students' writing competence. Keywords: Writing skill strategy, Text-oriented material, Mixed-method research.